PEMBERIAN WORKPLACE STRETCHING EXERCISE DAN MODIFIKASI KONDISI KERJA DAPAT MENURUNKAN KELUHAN MUSKULOSKLETAL DAN KELELAHAN PADA PEKERJA PEMBUAT DODOL TRADISIONAL DI DESA TAMBLANG – KABUPATEN BULELENG - Ketut Laksmi Puspa Dewi; Nyoman Adiputra; I Made Muliarta; Ketut Tirtayasa; I Putu Gede Adiatmika; I Wayan Bandem Adnyana (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2018)
The activity of traditional dodol stirrer workers is done with standing position. The stirring process is done monotonically and over a long period of 5 hours. This study aims to show that workplace stretching exercise administration and modification of working conditions may decrease musculoskeletal and fatigue complaintas in traditional dodol stirrer workers. The stirring tool (siut) used by the worker does not correspond to anthropomethry, causing a work with a bent position. This study was an experimental study, with the same subject design. Period I subjects were treated with conventional working condition. Period II subjects were treated with workplace stretching exercise administration and improved working conditions in the form of re-design the stirring tool(siut) of the dodol stirrer and active rest. Musculoskeletal complaints were measured by Nordic body map questionnaires on a 4 likert scale, working fatigue using 30 item rating scales. Analysis of the collected data is started with the descriptive analysis and the normality data tested using Shapiro-Wilk. Further, the data that has normal distribution are analyzed using t-paired and the data that has not a normal distribution are analyzed using Wilcoxon test. This study indicated that the administration of workplace stretching exercise and modification of working conditions can decreasing musculoskeletal decline of 18.3 % from the mean 12.67±0.50 to 5.59±0.52 and fatigue decreased by 18.5% from the mean 12.42±1.45 to 5.34±0.66 It can be concluded that the provision of workplace stretching exercise and modification of working condition can decrease musculoskeletal complaintas and fatigue of dodol stirrer workers. So it is advisable for the dodol making industry to applied this technique of exercise to minimize complaints due to the working process of stirring dodol.